2009
DOI: 10.1099/vir.0.006114-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of seven haplotypes of the caprine PrP gene at codons 127, 142, 154, 211, 222 and 240 in French Alpine and Saanen breeds and their association with classical scrapie

Abstract: In sheep, susceptibility to scrapie is mainly influenced by polymorphisms of the PrP gene. In goats, there are to date few data related to scrapie susceptibility association with PrP gene polymorphisms. In this study, we first investigated PrP gene polymorphisms of the French Alpine and Saanen breeds. Based on PrP gene open reading frame sequencing of artificial insemination bucks (n=404), six encoding mutations were identified at codons 127, 142, 154, 211, 222 and 240. However, only seven haplotypes could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
138
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(157 citation statements)
references
References 25 publications
14
138
1
4
Order By: Relevance
“…The genotype frequencies at codon 142 in these 200 goats were 40.0% II 142 , 46.5.0% IM 142 and 13.5% MM 142 (I, isoleucine; M, methionine). 1 Jeffrey and Spiropoulos, unpublished data.…”
Section: Herd and Case Historymentioning
confidence: 93%
See 1 more Smart Citation
“…The genotype frequencies at codon 142 in these 200 goats were 40.0% II 142 , 46.5.0% IM 142 and 13.5% MM 142 (I, isoleucine; M, methionine). 1 Jeffrey and Spiropoulos, unpublished data.…”
Section: Herd and Case Historymentioning
confidence: 93%
“…This is well established for sheep, but less well examined for goats [11]. The most common amino acid polymorphisms in British goat breeds are at codons 127 (glycine or serine), 142 (isoleucine or methionine), 143 (histidine or arginine) and 240 (proline or serine), and an association of polymorphisms at codons 142 and 143 with susceptibility and incubation period has been reported [1,2,10]. A comprehensive review of the goat PNRP gene polymorphisms and their association with disease has recently been published [31].…”
Section: Introductionmentioning
confidence: 99%
“…Encoding of serine instead of glycine at codon 127 has decreased the probability of clinical manifestation of the disease [86]. Isoleucine-methionine dimorphism at codon 142 has found to be associated both experimental [88] and natural infection [86,89]; furthermore, it is reported that [89] the presence of methionine-isoleucine as heterozygous at codon 142 has been provided resistance only in proline-proline homozygous animal at codon 240. Encoding of arginine at codon 143 has provided limited protection to natural scrapie [80].…”
Section: Resistance In Goatsmentioning
confidence: 99%
“…While the presence of asparagine instead of Serine or Aspartic acid at codon 146 has been found to be related to susceptibility to natural infection [78], it also has reported that the presence of Serine as heterozygous at the same codon has associated with the extended incubation period in oral challenging [90]. According to the results of various studies, arginine-histidine dimorphism at codon 154 has provided limited resistance [78,80,83,89]. The presence of glutamine/arginine as heterozygous at codon 211 has been found to Abbreviations of the amino acids: A, alanine; D, aspartic acid; F, phenylalanine; G, glycine; H, histidine; I, isoleucine; K, lysine; L, leucine; M, methionine; N, asparagine; P, proline; Q, glutamine; R, arginine; S, serine; T, threonine; V, valine; W, tryptophan.…”
Section: Resistance In Goatsmentioning
confidence: 99%
See 1 more Smart Citation